Papua New Guinea food price bulletin: April 2025 - International Food Policy Research Institute; Hayoge, Glen; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2025)
Download time series food price data, and build graphs and tables for over 20 different food crops at our food price database webpage: https://www.ifpri.org/project/fresh-food-price-analysis-papua-new-guinea Compared to Q4 2024, average prices of staples across the PNG markets decreased by 15 percent from January to March 2025 The price of a 1-kilogram bag of imported rice remained relatively stable between January and February 2025. Compared to Q4 2024, the average 1-kg bag of rice price increased by 6 percent in the first quarter of 2025. Compared to Q4 2024, Q1 2025 price trends of fresh vegetables were mixed across commodities. In Port Moresby, prices of English cabbage, carrot and choko-tips were 12 percent lower, while aibika and capsicum were 24 percent higher than January and February 2024. Compared to Q4 2024, prices of lemon, orange, pawpaw and pineapple in Goroka and Kokopo decreased on average by 15 percent in Q1 2025.